The structural and functional properties of polysaccharide foulants in membrane fouling. (April 2021) - Meng, Xianghao; Luosang, Duoji; Meng, Shujuan; Wang, Rui; Fan, Wenhong; Liang, Dawei; Li, Xiaohu; Zhao, Qian; Yang, Linyan
Abstract: Polysaccharide foulant is known to play a crucial role in membrane fouling, however the detailed influential mechanisms and the pertinence to specific structure of polysaccharides, as well as intermolecular interactions among them with and without divalent cation are still indistinct. In this study, seven polysaccharides including agarose, sodium alginate, carrageenan, pectin, starch, sodium carboxymethylcellulose (CMC) and xanthan gum, with different chain and molecular structures, were used as model foulants to investigate the role of structural and functional features of polysaccharides in membrane fouling. Two Hermia's models (classical and mass-transfer models) as well as the resistance-in-series model were used to analyze the fouling mechanism. Results show that the spatial configuration of foulant molecule is significant in membrane fouling which actually controls the resistance of gel layer formed on membrane. Polysaccharides with different properties show distinct fouling mechanisms which are in accordance with the four models described by Hermia respectively. Cations may change the interaction of polysaccharide foulant which further leads to the structural change of the gel layer. It turns out that mass-transfer model is more suitable for interpreting of crossflow filtration data. So far, little has been known about the effects of molecule structure of polysaccharides on membrane fouling. In this paper, we provide a basic database for polysaccharide fouling which will work as a theoretical basis for finding more effective measures to prevent and control membrane fouling. Graphical abstract: Image 1 Highlights: The spatial configuration of foulant molecule is significant in membrane fouling. The resistance of gel layer is controlled by interaction of polysaccharide foulant. Cations may change the interaction of polysaccharide foulant. Mass-transfer model is more suitable for interpreting of crossflow filtration data.